An external validation of C‐reactive protein reduction as a predictor of healing following laryngopharyngectomy. (10th August 2022) - James, Tobias W.; Edwards, Michael J.; Nieto, Hannah; Mehanna, Hisham; Pracy, Paul; Jennings, Christopher; Sharma, Neil; Nankivell, Paul
: